Increased serum soluble lectin-like oxidized low-density lipoprotein receptor-1 levels in patients with biopsy-proven nonalcoholic fatty liver disease - YILMAZ, YUSUF (BAISHIDENG PUBLISHING GROUP INC, 2015)
AIM: To analyze the relationship between the serum lectin-like oxidized low-density lipoprotein receptor-1 (LOX-1) levels and clinical and histopathological features of biopsy-confirmed nonalcoholic fatty liver disease (NAFLD) patients. METHODS: Fifty-three consecutive, biopsy-proven NAFLD patients (31 males and 22 females, mean age 42.5 +/- 9.6 years) and 26 age-and gender-matched, healthy controls (14 males and 12 females, mean age 39 +/- 10.7 years) were included. The patients with NAFLD were consecutive patients who had been admitted to the hepatology outpatient clinic within the last year and had been diagnosed with NAFLD as the result of liver biopsy. The healthy controls were individuals who attended the outpatient clinic for routine health control and had no known chronic illnesses. The histological evaluation was conducted according to the NAFLD activity scoring system recommended by The National Institute of Diabetes and Digestive and Kidney Diseases Nonalcoholic Steatohepatitis Clinical Research Network. The serum LOX-1 levels were measured using an ELISA kit (Life Science Inc. USCN. Wuhan, Catalog No. E1859Hu) in both patients and healthy controls. A receiver operating characteristic (ROC) curve analysis was used to identify the optimal cutoff value of LOX-1 and thereby distinguish between patients with nonalcoholic steatohepatitis (NASH) and healthy controls. A P-value < 0.05 was considered statistically significant. RESULTS: NAFLD and healthy control groups were similar in terms of age and sex. NAFLD patients consisted of 8 patients with simple steatosis (15%), 27 with borderline NASH (51%) and 18 with definitive NASH (34%). Metabolic syndrome was found in 62.2% of the patients with NAFLD. The mean serum LOX-1 level in biopsy-proven NAFLD patients was 8.49 +/- 6.43 ng/mL compared to 4.08 +/- 4.32 ng/mL in healthy controls (P = 0.001). The LOX-1 levels were significantly different between controls, simple steatosis and NASH (borderline+definite) cases (4.08 +/- 4.32 ng/mL, 6.1 +/- 6.16 ng/mL, 8.92 +/- 6.45 ng/mL, respectively, P = 0.004). When the cut-off value for the serum LOX-1 level was set at 5.35 ng/mL, and a ROC curve analysis was performed to distinguish between steatohepatitis patients and controls; the sensitivity and specificity of the serum LOX-1 level were 69.8% and 69.2%, respectively. CONCLUSION: The serum LOX-1 levels were significantly higher in NAFLD patients than in healthy controls. Additionally, the serum LOX-1 levels could differentiate between steatohepatitis patients and healthy controls.
Keywords: Insulin resistance; Liver fibrosis; Metabolic syndrome; Nonalcoholic fatty liver disease; Steatohepatitis; ASSOCIATION; LOX-1